Pendidikan Akhlak Perspektif Al-Qur’an - Evi Febriani; Citra Oktaviani; Muhamad Kumaidi (Jurnal Syntax Admiration, 2024)
The purpose of this study is to discuss morals in the perspective of Islamic education. The type of research used in this study is a descriptive method with a research approach using qualitative methods. As for this research method, it uses the method of literature review or library research on books, scientific journals, the Qur'an and Hadith and other sources. The results of this study explain that morals have a very important role to learn and to be applied in everyday life. Morals have such a high position and are considered to be the key determinants in educational success. The role of morals according to the perspective of Islamic education refers to human behavior, attitudes and morals which include aspects such as ethics, morals and manners regulated in Islamic religious teachings. Morals in Islamic education are useful to prepare humans towards a prosperous life both in the world and in the hereafter.